Tradução comentada do conto "The outsider", de H. P. Lovecraft - Leal, Fernanda Felipe (2020)
This work aims to propose a translation with commentary into Brazilian Portuguese of the short story The Outsider, which is part of weird genre, by the American writer Howard Phillips Lovecraft (1890-1937). Besides preparing the ground for science fiction, the author also encouraged a renew in horror genre by using elements other than those related to supernatural what contributed to the establishment of weird fiction as new realm in the American fantastic literature. In Brazil, the amount of translation with commentary of H.P. Lovecraft’s work may reveal that, despite his literary relevance, the author still remains marginalized in that field. Therefore, this study proposes a translation with commentary of the aforementioned short story that was written around 1921 but only published in 1999 as part of the book The Call of Cthulhu and Other Weird Stories, in Penguin Classics’ series. That book is the first revised, corrected, and definitive anthology of Lovecraft’s works and that short story represented a milestone in his career as a fiction writer. In addition, his writing style and some translation options based on Lawrence Venuti's cultural strategy of foreignization will be presented to assess if that strategy could change the translator's invisibility situation, in opposition to the cultural strategy of domestication, which is perceived by Venuti as pernicious.